Observational study on association between serum thyroid stimulating hormone and thyroid malignancy - K., Arun; K., Santhosh Nayak; Gowda, Suhas (International Surgery Journal, 2017)
Background: Thyroid cancer is the most common endocrine malignancy and its incidence continues to rise. Thyroid carcinoma in most cases presents clinically as a solitary nodule or as a dominant nodule within a multinodular thyroid gland. There are a number of well-established of predictors of malignancy in thyroid nodules. More recently studies have suggested that higher concentration of TSH, even within the normal range are associated with subsequent diagnosis of thyroid cancer in patients with thyroid nodules and even higher serum TSH levels have been found associated with advanced stages of thyroid cancer. Objectives were to determine the association between serum thyroid stimulating hormone (TSH) concentration and thyroid cancer and to estimate serum TSH levels in different stages of thyroid malignancy. Methods: A hospital based observational study was conducted in a tertiary care hospital for a period of 2 year. 120 patients presenting with thyroid nodule without an overt thyroid dysfunction during the study period were included in the study. Chi-square was used as test of significance. Independent t test was the test of significance for quantitative data between two groups. Results: In the study majority of thyroid cancer patients (106 out of 120) had serum TSH concentrations ranging 1.71mIU/L-5.5mIU/L i.e. within normal range but towards higher range. Mean serum TSH concentrations was significantly high in advanced stages of carcinoma. Mean Serum TSH was high in Stage III and Stage IV (5.17±1.36mIU/l) compared to stage I and II (4.03±1.87mIU/l). Conclusions: The study concludes that TSH levels were in the Upper reference range in majority of thyroid malignancies and high levels of serum TSH concentrations associated with advanced stage of thyroid cancer.